The History of Woman Suffrage, Volume V - Harper, Ida Husted, 1851-1931 (Salt Lake City, UT : Project Gutenberg, 2009)
"The History of Woman Suffrage, Volume V" by Ida Husted Harper is a historical work published in 1922. This volume forms part of a monumental six-volume series documenting the American women's suffrage movement from its origins through the ratification of the Nineteenth Amendment in 1920. Spanning over 5,700 pages total, the series serves as the primary source for the movement's history, written from the perspective of leaders Susan B. Anthony and Elizabeth Cady Stanton, preserving crucial letters, speeches, and firsthand accounts of the fight for women's voting rights. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Woman_Suffrage
This volume covers 1900-1920.
Release date is 2009-08-31
E-text prepared by Richard J. Shiffer and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Women -- Suffrage -- United States -- History; Women -- Suffrage -- History; Women's rights -- United States -- History; Women's rights -- History